Monitoring Survivability and Infectivity of Porcine Epidemic Diarrhea Virus (PEDv) in the Infected On-Farm Earthen Manure Storages (EMS) - Tun, Hein M.; Cai, Zhangbin; Khafipour, Ehsan (Frontiers in Microbiology, 2016)
In recent years, porcine epidemic diarrhea virus (PEDv) has caused major epidemics, which has been a burden to North America's swine industry. Low infectious dose and high viability in the environment are major challenges in eradicating this virus. To further understand the survivability and infectivity of PEDv in the infected manure, we performed longitudinal monitoring in two open earthen manure storages (EMSs; previously referred to as lagoon) from two different infected swine farms identified in the province of Manitoba, Canada. Our study revealed that PEDv could survive up to nine months in the infected EMS after the initial outbreak in the farm. The viral load varied among different layers of the EMS with an average of 1.1 × 105 copies/ml of EMS, independent of EMS temperature and pH. In both studied EMSs, the evidence of viral replication was observed through increased viral load in the later weeks of the samplings while there was no new influx of infected manure into the EMSs, which was suggestive of presence of potential alternative hosts for PEDv within the EMSs. Decreasing infectivity of virus over time irrespective of increased viral load suggested the possibility of PEDv evolution within the EMS and perhaps in the new host that negatively impacted virus infectivity. Viral load in the top layer of the EMS was low and mostly non-infective suggesting that environmental factors, such as UV and sunlight, could diminish the replicability and infectivity of the virus. Thus, frequent agitation of the EMS that could expose virus to UV and sunlight might be a potential strategy for reduction of PEDv load and infectivity in the infected EMSs.